First records of Dentridactylinae (Orthoptera: Tridactylidae) from Colombia, with description of two new species of Dentridactylus Günther - Baena-Bejarano, Nathalie; Heads, Sam W. (Zootaxa, 2018)
Two new species of Dentridactylus Günther (Orthoptera: Tridactylidae) are described and illustrated: Dentridactylus quadratus sp. nov. and Dentridactylus truncatus sp. nov. The new species represent the first record of the subfamily Dentridactylinae from Colombia and the second record for the Americas. Both come from the south of the country and are readily separated from congeners by their larger body size; D. quadratus sp. nov. is further delimited by the quadrate outline of the epiproct, and D. truncatus sp. nov. by the epiproct with lateral lobes and lateral margin of epiproct not indented. Keys for the identification of species in the Americas are provided.